Nuzi Notes 23. Problematische SMN-Nummern der Texte EN 9/1-3 - Fincke, Jeanette (SCCNH)
Nuzi Notes 26. ?ušu??e "(Zier-)Gürtel": ebd., 356-357; Nuzi Notes 27. pizipsumma ep?šu: ebd., 357-361; Nuzi Notes 31. SMN 2799 and one unnumbered fragment joined to EN 9/2 455: ebd., 365-366.